Upaya Meningkatkan Gaya Pacaran Sehat Dikalangan Remaja Melalui Layanan Bimbingan Kelompok Siswa SMP - Utari Gusti Apriani; Mahaardhika I Made (Jurnal Bimbingan dan Konseling Indonesia, 2023)
The implementation of guidance and counseling in school learning is very necessary, considering that students are in the adolescent stage. At this stage, a person experiences many physical and psychological transitions that should affect their behavior, including students' career insights and readiness. The purpose of this study was to determine the effectiveness of podcast-based classical guidance services to prepare students' career insights and planning. This study used a class action research method with a total of 29 students. The research was conducted through 2 cycles which began with the stages of planning, action implementation, observation, and reflection in each cycle. Data analysis was carried out qualitatively by describing the facts collected and presented in the form of descriptions. The result of this study was an increase in career insight and readiness in students after being given podcast-based classical guidance services. Based on the results of the implementation of classroom action research that has been carried out, it is hoped that in the future counseling teachers can become one of the alternative methods of implementing counseling at school.